Prevalence of COVID-19 infection in black people in primary health care, hospital units and intensive care units: a protocol for a systematic review and meta-analysis - Talita Araujo de Souza; Pedro Henrique Alcântara da Silva; Maria Helena Rodrigues Galvão; Aryelly Dayane da Silva Nunes; Dalyanna Mildred de Oliveira Viana Pereira; Arthur de Almeida Medeiros; Isabelle Ribeiro Barbosa; Gilson de Vasconcelos Torres (BMJ Open)
Introduction COVID-19 pandemic has affected people all over the world. In this context, health disparities are already evident in becoming ill and dying from this condition, further accentuating historical racial inequalities.Methods and analysis This protocol will be developed based on the recommendations of Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols. For this, searches will be carried out in PubMed, Web of Science, Scopus, Lilacs and ScienceDirect databases searching for cross-sectional studies that assessed the prevalence of black people with COVID-19 at different levels of complexity. All cross-sectional studies that analysed the prevalence of COVID-19 in black people assisted in primary care, hospital wards and intensive care units will be included. The research will be carried out by two independent researchers who will identify the articles; they will exclude duplicate studies. Through blind evaluation, they will select the articles using the Rayyan QCRI application. The instrument proposed by Downs and Black will be used to assess the risk of bias. The meta-analyses will be performed according to the data conditions included.Ethics and dissemination For this study’s development, there is no need for an ethical appraisal considering that it is a systematic review that will use secondary studies. This study’s findings will be disseminated through peer-reviewed publications, conference presentations and condensed summaries for main stakeholders and partners in the field. The database search is expected to begin on 1 February 2021. It is expected to complete the entire review process by 30 October 2021Trial registration number CRD42020209079.